2020
DOI: 10.1128/mbio.02094-20
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleoid Occlusion Protein SlmA Binds to Lipid Membranes

Abstract: Protection of the chromosome from scission by the division machinery during cytokinesis is critical for bacterial survival and fitness. This is achieved by nucleoid occlusion, which, in conjunction with other mechanisms, ensures formation of the division ring at midcell. In Escherichia coli, this mechanism is mediated by SlmA, a specific DNA binding protein that antagonizes assembly of the central division protein FtsZ into a productive ring in the vicinity of the chromosome. Here, we provide evidence supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Previous results have shown that FtsZ·SlmA·SBS condensates accumulate at the lipid interface when encapsulated in lipid-stabilized microdroplets . Interestingly, SlmA binds to lipid membranes, as recently revealed by biochemical membrane-reconstitution approaches . These findings suggest that membrane surfaces may control biomolecular phase separation in bacteria, as shown already in several eukaryotic systems, and may help to modulate FtsZ spatiotemporal organization inside bacterial cells.…”
supporting
confidence: 56%
“…Previous results have shown that FtsZ·SlmA·SBS condensates accumulate at the lipid interface when encapsulated in lipid-stabilized microdroplets . Interestingly, SlmA binds to lipid membranes, as recently revealed by biochemical membrane-reconstitution approaches . These findings suggest that membrane surfaces may control biomolecular phase separation in bacteria, as shown already in several eukaryotic systems, and may help to modulate FtsZ spatiotemporal organization inside bacterial cells.…”
supporting
confidence: 56%
“…Although in vitro studies, including investigations of SBS-SlmA interaction, , are often performed in chloride salts, changing from potassium chloride to potassium glutamate can enhance the protein–DNA interaction in vitro by stabilizing protein–DNA complexes . In addition, glutamate as anion is also physiologically more relevant .…”
Section: Resultsmentioning
confidence: 99%
“…For example, nucleoid occlusion and other unknown factors may assist in positioning cell division. SlmA, bound directly to lipid membranes and DNA, could play a role in the spatiotemporal modulation of Z-ring assembly by narrowing the division site at midcell 59 .…”
Section: Discussionmentioning
confidence: 99%